Correlation Between Gender and HBA1C of Diabetic Patients with Thyroid Dysfunction - Jarallah, Fatima Mohamed; Algdar, Ahmed A. (The 1st International Conference On Basic Sciences & Its Applictionss, 2024)
The thyroid gland secretes thyroid hormones, which are involved in controlling metabolism, growth, and development. They also affect the heart, muscles, and digestive system. Numerous health issues can result from thyroid dysfunction, including diabetes, dementia, and obesity. The data of 83 diabetic patients were obtained from the Endocrine and Diabetic Center Zliten (2023). The result showed that, the HbA1c and sex has a correlation of (0.021), the HbA1c and TSH has a correlation of (0.515), indicating that the relationship is not significant , and the HbA1c and age has a correlation of (0.439), suggesting that there is a weak relationship. The study concluded that there is no significant relationship between gender and HbA1c of diabetic patients with thyroid dysfunction.